Finite Element Programme Development for the Analysis of Precast Flooring and Roofing System - Wong, Jern Nee (2004)
At the initial stage of this study an attempt was made to write a computer programme for the analysis and design of precast floor slabs on the FORTRAN language, which is compatible with FORTRAN 90 Power Station. The programme considers various types of precast reinforced concrete slabs such as solid slab (one-way and two-way), hollow core slab, ribbed slab and composite slab. The programme consists of a main and several subroutines. The programme was written according to BS 8110 and was verified by using it to analyse a few examples. The software is capable of analysing and designing different floor slabs with a provision for generating the optimal crosssection and plotting the cross section graphically. Further, the effect of different design parameters on the solid slab, hollow slab and ribbed slab design had been presented. One of the main objectives of this study was the development of a finite element code using the semi-loof beam and shell elements. The application of these elements to model the precast flooring and roofing system was illustrated. The validity of the developed programme was established by analysing some benchmark problems and comparing the results with those from a commercial package. The results indicate that the use of the semi-loof elements resulted in a powerful programme, which is suitable for the analysis of complex shell type structures. Another primary objective of this investigation was the analysis of a composite slab, which consisted of precast and insitu layers. There was a need to model two different materials along with their interface characteristic. An interface element sandwiched between two 16-noded isoparametric brick element has been formulated. This interface element was used in an existing three dimensional finite element package. The behaviour of the composite slab under load with respect to displacements, stresses and strains was studied. It was found that it was important to model frictional behaviour between the two different materials as in composite slabs.